2012
DOI: 10.1017/s0007114511006842
|View full text |Cite
|
Sign up to set email alerts
|

Control of voluntary feed intake in fish: a role for dietary oxygen demand in Nile tilapia (Oreochromis niloticus) fed diets with different macronutrient profiles

Abstract: It has been hypothesised that, at non-limiting water oxygen conditions, voluntary feed intake (FI) in fish is limited by the maximal physiological capacity of oxygen use (i.e. an 'oxystatic control of FI in fish'). This implies that fish will adjust FI when fed diets differing in oxygen demand, resulting in identical oxygen consumption. Therefore, FI, digestible energy (DE) intake, energy balance and oxygen consumption were monitored at non-limiting water oxygen conditions in Nile tilapia fed diets with contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 54 publications
6
72
0
1
Order By: Relevance
“…An enhanced oxidative metabolism over the long term has been suggested to impart putative negative effects (e.g., the buildup of reactive oxygen species) on the animal (27,28). In view of the above findings, we previously proposed a role of oxygen consumption in the control of voluntary feed intake in Nile tilapia fed diets highly varying in macronutrient composition (11). In that study, Nile tilapia linearly adjusted the feed intake (DEI) depending on the diet-induced differences in oxygen use and, moreover, had a similar oxygen consumption in some of the diet groups, which suggests that perhaps physiological factors related to oxygen consumption constrained the feed intake.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…An enhanced oxidative metabolism over the long term has been suggested to impart putative negative effects (e.g., the buildup of reactive oxygen species) on the animal (27,28). In view of the above findings, we previously proposed a role of oxygen consumption in the control of voluntary feed intake in Nile tilapia fed diets highly varying in macronutrient composition (11). In that study, Nile tilapia linearly adjusted the feed intake (DEI) depending on the diet-induced differences in oxygen use and, moreover, had a similar oxygen consumption in some of the diet groups, which suggests that perhaps physiological factors related to oxygen consumption constrained the feed intake.…”
Section: Introductionmentioning
confidence: 96%
“…It has often been suggested that fish, like other animals, adjust their voluntary feed intake according to the digestible energy content of the diet in order to meet a predefined energy requirement (2)(3)(4). However, recent findings in rainbow trout (5)(6)(7)(8)(9)(10) and other teleosts (6,11,12) contradict the notion that feed intake is adjusted to have a constant digestible energy intake (DEI) 6 . Similarly, the demand for a target lean growth or protein deposition rather than for a predefined energy requirement has been proposed to regulate feed intake in fish (8,10,13,14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that excess dietary protein and lipid levels can negatively influence the SGR and FCR in fish (Brown et al 1992;Hatlen et al 2007;Peres and Oliva-Teles 1999;Saravanan et al 2012). Excess dietary lipid increases adiposity, which is thought to exert a negative feedback on feed intake via lipostatic regulation mechanisms (Johansen et al 2002).…”
Section: Discussionmentioning
confidence: 99%